ANCA Vasculitis and Hemophagocytic Lymphohistiocytosis following a Fecal Microbiota Transplant - Adam Amlani; Amy Bromley; Aurore Fifi-Mah (Case Reports in Rheumatology)
A 69-year-old female with antisynthetase syndrome, a history of multiple recurrent infections, and documented previous negative titres for anti-neutrophil cystoplasmic antibody (ANCA) suddenly developed a de novo MPO-ANCA-associated glomerulonephritis three weeks after a fecal microbiota transplantation (FMT) for recurrent Clostridium difficile infections. Six months following her FMT and less than two weeks following treatment for urosepsis, she developed severe cholestasis, a markedly elevated ferritin and hypertriglyceridemia. An initial liver biopsy was suggestive of drug-induced liver injury and thus she was treated with supportive care. After she failed to improve, a second liver biopsy supported the diagnosis of hemophagocytic lymphohistiocytosis (HLH). This case highlights difficulties surrounding the early diagnosis of HLH and also questions the role of FMT and/or recurrent infections as a trigger for ANCA-associated vasculitis.